Mathematical Modeling of The Biodegradation of Phenol from Industrial Effluents Using Immobilized Pseudomonas putida (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Synthetic chemicals are extremely harmful, particularly those man-made ones. Models are used to describe the behavior of microorganisms under different physical or chemical conditions such as temperature, pH, and water activity. Phenol is one of the potentially hazardous synthetic industrial contaminants capable of causing deteriorating effects in humans. In this paper, for the first time we present different kinetics models such as Von Bertalanffy, Baranyi-Roberts, modified Schnute, modified Richards, modified Gompertz, modified Logistics and the most recent Huang were used to get values for the above kinetic constants or parameters from simultaneous biodegradation of phenol from industrial effluents using immobilized Pseudomonas putida. All the curves present the best models with highest adjusted R2 value with the lowest RMSE and AICc value. The Accuracy and Bias Factors values were close to unity (1.0). Nearly all of the models best fit the curves indicating that Pseudomonas putida growth on phenol can be described mathematically the modelling parameters obtained can be utilized for predicting bioremediation of phenols in batch culture and perhaps in the future will be valuable in modelling growth eon industrial effluent containing phenol.
Keywords: Phenol, Pseudomonas putida, mathematical modelling, growth